Kecerdasan Emosional Siswa dalam Pemilihan Sekolah Lanjutan - Undriani, Yulia; Yusri, Yusri; Sukmawati, Indah (Konselor, 2015)
Emotional intelligenceplays an important rolein education, one of themin theschoolelection. Emotionallyintelligentstudentsselect schoolsaccording totheir owndesiresand interestsandtalents. In factthere aresomestudentswho indicatedlessemotionallyintelligent, whichis stilldependent onhis parentsandwent along witha friendinhigh schoolelection, causingdisappointmentin himafterentering theselected schools. The purposeof researchtodescribe theemotional intelligenceof studentsin theschoolelectionsinSMK4Padang. Results ofthe studyrevealedthat(1) the emotionalintelligenceof studentsin theschoolelectionsfrom the aspects ofthe bulkidentify emotionsin middle category(2) aspects ofmanagingemotionsmostlyin middle category(3) aspects ofmotivating yourselfto beinthe medium category. From the research resultssuggestedTeacherGuidanceandCounseling/Counselorsprovideguidanceandcounselingservicesthatcanminimizethe lessintelligentstudentsemotionally, so thatstudentscandevelop the potentialin him. The servicescanbe giventhatthe serviceinformation, servicecontentmastery, andgroup counselingservicesthatmatterrelating toemotional intelligenceservices. It can also begivenindividualcounselingservicesfor students who have less troubleemotionallyintelligent. Thenit is also suggestedtohomeroom, principals, andschoolpersonnelin order tocooperatein identifyingandprovidinggreat attentionto studentswhoare lessemotionallyintelligent.